Tanzania 2023 - Ham, Anthony; Eveleigh, Mark; Fitzpatrick, Mary; Mahinya, Nasibu (Lonely Planet guidebooks., 2023)
Wildlife, beaches, Mt. Kilimanjaro, Zanzibar Archipelago--Tanzania has these and more wrapped up in one adventurous, welcoming package. Now fully updated, the #1 bestselling guide to Tanzania contains relevant information on what to see and do, as well as full-colour images and maps.